Defining the semantics of rule-based web applications through model-driven development - Cańadas, Joaquín; Palma, José; Túnez, Samuel (Zielona Góra: Uniwersytet Zielonogórski)
Rule languages and inference engines incorporate reasoning capabilities to Web information systems. This paper presents an approach for the specification and development of Web applications performing the usual functionalities of data management and incorporating a rule engine for reasoning capabilities. The proposed approach is based on the definition of a high-level representation of the semantics of rule-based applications through a formalism for conceptual modeling combining lightweight ontologies and production rules
Keywords: model-driven development; rule-based systems; Web applications